Clinical profile of patients with post-caesarean wound infection: experience of Patan Hospital, Nepal (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Would infection following caesarean delivery adds physical, psychological, and health burden to individual and health care system. This hospital based study aim to determine the rate of infection, the risk factors, pathogens and antibiotic sensitivity.Method: A prospective study was carried out to analyze the wound infection in women following caesarean delivery in the Department of Obstetrics and Gynecology, Patan Hospital, Nepal, between January 2018 to December 2018. The study was approved from the institutional review committee. Clinicodemographic data during perinatal period of caesarean delivery were descriptive analyzed in relation to wound infection.Result: Wound infection occurred in 102 (3.1%)of 3285 caesarean section (of total 7131 deliveries during the study period. The caesarean SSI rate was 3.1%, all were incisional SSI (84 superficial and 18 deep) and there were no organ-space SSI. Majority (81.3%) SSI cases were detected in emergency LSCS. Coagulase Negative Staphylococci was the most common organism isolated from wound swab. Routine postoperative antibiotics did not have a major impact in reducing wound infection rate. Multiple per vaginal examinations, prolonged rupture of membrane and staples for skin closure were more commonly associated with SSI.Conclusion: Reduction in caesarean rate is the major key factor for decreasing the post caesarean wound infection. Protocol should be developed and strictly implemented by all the health care professionals in order to minimize and prevent the infection rate after caesarean section.